Complete response of huge buccal malignant melanoma in an octogenarian patient to arterial chemotherapy. Issue 10 (22nd June 2015) - Wu, Chih‐Feng; Wu, Chieh‐Shan; Yu, Wei‐Wen; Huang, Ming‐Yii
Abstract: Background: Primary oral mucosal melanoma is uncommon. However, it is an aggressive entity, and the absence of a standardized treatment protocol makes for an extremely poor prognosis. Methods: We described the clinical course and treatment by arterial chemotherapy of an 87‐year‐old patient with nonresectable huge buccal malignant melanoma. Continuous intra‐arterial infusion of fluorouracil (50 mg/24 hours) and 1 intermittent weekly 10‐mg shot of cisplatin were given. Results: The patient with oral melanoma presented with a roughly 6‐ × 4‐cm exophytic mass that was noticed on the right buccal mucosa. The buccal tumor regressed dramatically until complete disappearance of the tumor mass was achieved at 2.5 months after intra‐arterial chemotherapy was initiated. In total, 2880 mg of fluorouracil and 80 mg of cisplatin were administrated. The side effects of intra‐arterial chemotherapy were mild and tolerable. Conclusion: Our data demonstrate that intra‐arterial chemotherapy could be an alternative treatment for nonresectable buccal malignant melanoma. © 2015 Wiley Periodicals, Inc. Head Neck 37: E134–E138, 2015